Hepatic Sel1L‐Hrd1 ER‐associated degradation (ERAD) manages FGF21 levels and systemic metabolism via CREBH. (2nd November 2018) - Bhattacharya, Asmita; Sun, Shengyi; Wang, Heting; Liu, Ming; Long, Qiaoming; Yin, Lei; Kersten, Sander; Zhang, Kezhong; Qi, Ling
Abstract: Fibroblast growth factor 21 (Fgf21) is a liver‐derived, fasting‐induced hormone with broad effects on growth, nutrient metabolism, and insulin sensitivity. Here, we report the discovery of a novel mechanism regulating Fgf21 expression under growth and fasting‐feeding. The Sel1L‐Hrd1 complex is the most conserved branch of mammalian endoplasmic reticulum (ER)‐associated degradation (ERAD) machinery. Mice with liver‐specific deletion of Sel1L exhibit growth retardation with markedly elevated circulating Fgf21, reaching levels close to those in Fgf21 transgenic mice or pharmacological models. Mechanistically, we show that the Sel1L‐Hrd1 ERAD complex controls Fgf21 transcription by regulating the ubiquitination and turnover (and thus nuclear abundance) of ER‐resident transcription factor Crebh, while having no effect on the other well‐known Fgf21 transcription factor Pparα. Our data reveal a physiologically regulated, inverse correlation between Sel1L‐Hrd1 ERAD and Crebh‐Fgf21 levels under fasting‐feeding and growth. This study not only establishes the importance of Sel1L‐Hrd1 ERAD in the liver in the regulation of systemic energy metabolism, but also reveals a novel hepatic "ERAD‐Crebh‐Fgf21" axis directly linking ER protein turnover to gene transcription and systemic metabolic regulation. Synopsis: Nuclear receptor PPARα and transcription factor CREBH control FGF21 expression in the liver. The Sel1L‐Hrd1 ER‐associated degradation (ERAD) complex regulates FGF21 levels by controlling ubiquitination and turnover of CREBH under both fasting‐feeding and normal growth in mice. Liver‐specific SEL1L‐knockout mice exhibit growth retardation, increased insulin sensitivity, reduced adiposity, and resistance to diet‐induced obesity. Hepatic SEL1L deficiency induces FGF21 gene transcription and increases FGF21 circulating levels responsible for altered metabolic profile. ER‐resident transcription factor CREBH is a bona fide endogenous substrate of SEL1L‐HRD1 ERAD and links hepatic ERAD to FGF21 gene transcription. Hepatic ERAD‐Crebh‐Fgf21 axis regulate key metabolic states in mice. Abstract : Conditional deletion of the ER‐associated degradation factor SEL1L in mouse livers alters key metabolic states in the whole organism via dysregulation of the FGF21 hepatokine.